2018
DOI: 10.3389/fphar.2018.00028
|View full text |Cite
|
Sign up to set email alerts
|

Asiaticoside Attenuates Cell Growth Inhibition and Apoptosis Induced by Aβ1-42 via Inhibiting the TLR4/NF-κB Signaling Pathway in Human Brain Microvascular Endothelial Cells

Abstract: Alzheimer’s disease (AD) is a very common progressive neurodegenerative disorder with the highest incidence in the world. Dysfunction of the blood–brain barrier (BBB) may be responsible for the pathogenesis and pathology of AD for abnormally transporting amyloid-β (Aβ, the main component of the senile plaques) from the sera into the central nervous system. Aβ peptides induce apoptosis in human brain microvascular endothelial cells (hBMECs), the main component of BBB. Apoptosis in neuronal cells plays a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…It is known that antioxidants have an effective role in ameliorating radiation-induced oxidative injuries [15]. AC has been cells [6,23]. In our study, we found that AC significantly restored the level of serum T-AOC caused by radiation, and mitigated radiation-induced DNA damage, indicating that AC might act as a radio-protectant for the treatment of side effects produced by radiation therapy.…”
Section: Discussionsupporting
confidence: 60%
“…It is known that antioxidants have an effective role in ameliorating radiation-induced oxidative injuries [15]. AC has been cells [6,23]. In our study, we found that AC significantly restored the level of serum T-AOC caused by radiation, and mitigated radiation-induced DNA damage, indicating that AC might act as a radio-protectant for the treatment of side effects produced by radiation therapy.…”
Section: Discussionsupporting
confidence: 60%
“…Once microglia are activated, IκB-α is separated and transferred from the cytoplasm to the nucleus, resulting in transcription and expression of inflammatory factors [49]. NF-κB is expressed in nearly all cells and plays an important role in the activation of the M1 microglial phenotype [50]. Our results further showed that betaine interacted with the IKK complex and specifically targeted its IKK-β subunit, thereby protecting the IκB subunit from LPS-mediated inflammatory stimulus-induced phosphorylation and subsequent proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It dissolves in methanol, ethanol, and water. Relevant literature on the nervous system demonstrated that C. asiatica and its triterpenes could be used to relieve a variety of neurological diseases, but the most researched are improve Alzheimer's disease (AD) (Song et al, 2018) and Parkinson's disease (Nataraj et al, 2017b) (Table 2). The pathogenesis of AD and Parkinson's disease involve neuroinflammatory activities (Gelders et al, 2018), oxidative stress (Jiang et al, 2016), mitochondrial dysfunction (Morais and De Strooper, 2010), and dysfunction in brain-derived neurotrophic factor (Mohammadi et al, 2018).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 99%